Introducing the socialbot: a novel touchpoint along the young adult customer journey. (25th May 2020) - Wilson-Nash, Carolyn; Goode, Amy; Currie, Alice
Abstract : Purpose: The purpose of this paper is to contribute to the special issue theme by exploring customer response to automated relationship management tactics on social media channels. Design/methodology/approach: A total of 17 in-depth interviews of young adults, ranging from the age of 19 to 26, were conducted. From this, customer journey maps were compiled incorporating socialbots as a valuable touch point along the service delivery cycle. Findings: The research frames the socialbot as a valued customer service agent to young adults with some favouring this over telephone and email communication methods. Younger consumers respond positively to the quick resolution offered by the socialbot mechanism with most acknowledging that the bot is only able to manage simplified requests. Human-to-human customer relationship management is preferential when the query reaches critical mass. Research limitations/implications: Socialbots on Facebook Messenger provided the research context for this study; therefore, other platforms and owned website bots should be considered in future studies. Practical implications: This research identifies the younger generation as a key target market for the development of customer service-related bots. Originality/value: To the best of the authors' knowledge, this is the first study to examine the socialbot as an automated touch point in the customer journey and contributes knowledge to the growing body of literature focussed on artificial intelligence in customer service. Moreover, it provides valuable qualitative insights into how socialbots influence the customer experience and related outcome measures.